A kitten tale - Rohmann, Eric. (New York : Alfred A. Knopf, 2008)
As four kittens who have never seen winter watch the seasons pass, three of them declare the reasons they will dislike snow when it arrives, while the fourth cannot wait to experience it for himself.
Keywords: Snow -- Juvenile fiction; Seasons -- Juvenile fiction; Kittens -- Juvenile fiction; Snow -- Fiction; Seasons -- Fiction; Cats -- Fiction; Picture books for children